FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PETANI BERUSAHATANI PADI DI DESA SENDANGAN KECAMATAN KAKAS KABUPATEN MINAHASA - Sitty M. Panurat; Oktavianus Porajouw; Agnes F. Loho; Grace A.J. Rumagit (COCOS, 2014)
ABSTRACTThe study aims to determined factors that influence the interests of farmer in rice farming in the Sendangan Village and to determine the influence of each factors on interets of rice farmer.The data used is primary data collected from 36 farmers using a questionnaire that had been developed . The analysis used in this study is a multiple linear regression analysis , using the SPSS 16 software tools . Secondary data obtained from agencies associated with this research that the Central Bureau of Statistics and the Office of the District of North Sulawesi Kakas .The results showed that there were factors the interests of farmers are land area, experience, income, and education assistance. Land area and income very significant effect on the interest of farmers. While the assistance and experience significant effect on the interest, education influence otherwise no significant effect on the interest. With the value of the contribution of determination R2 are the factors affecting land use, experience, income, and education of 72%.